Instrument of Memory Encounters with the Wandering Jew - Lampert-Weissig, Lisa (University of Michigan Press, 2024)
How can immortality be a curse? According to the Wandering Jew legend, as Jesus made his way to Calvary, a man refused him rest, cruelly taunting him to hurry to meet his fate. In response, Jesus cursed the man to wander until the Second Coming. Since the medieval period, the legend has inspired hundreds of adaptations by artists and writers. Instrument of Memory: Encounters with the Wandering Jew, the first English-language study of the legend in over fifty years, is also the first to examine the influence of the legend's medieval and early modern sources over the centuries into the present day. Using the lens of memory studies, the work shows how the Christian tradition of the legend centered the memory of the Passion at the heart of the Wandering Jew's curse. Instrument of Memory also shows how Jewish artists and writers have reimagined the legend through Jewish memory traditions. Through this focus on memory, Jewish adapters of the legend create complex renderings of the Wandering Jew that recognize not only the entanglement of Jewish and Christian memory, but also the impact of that entanglement on Jewish subjects. This book presents a complex, sympathetic, and more fully realized version of the legend while challenging the limits of the presentism of memory studies.